Atopic skin diathesis rather than atopic dermatitis is associated with specific contact allergies - Forkel, Susann; Cevik, Naciye; Schill, Tillmann; Worm, Margitta; Mahler, Vera; Weisshaar, Elke; Vieluf, Dieter; Pfützner, Wolfgang; Löffler, Harald; Schön, Michael P.; Geier, Johannes; Buhl, Timo (Journal der Deutschen Dermatologischen Gesellschaft, 2021)
Background The association of atopic dermatitis (AD) and allergic contact dermatitis has been a matter of considerable uncertainty. Study results range from lack of any association to increased sensitization for multiple allergens, but fail to identify consistent allergen associations. Objective We studied a large patch test cohort of patients stratified by their atopic skin diathesis using the Erlangen Atopy Score (EAS), independent of active skin disease. Methods Retrospective multi-center data analysis from five departments of dermatology in Germany with 4,509 patients. Patients were grouped as “no atopic skin diathesis” (n = 2,165) and “atopic skin diathesis” (n = 1,743), according to EAS. Results Significantly more individuals with atopic skin diathesis showed at least one positive patch test reaction to the baseline series compared to individuals without atopic skin diathesis (49.1 % vs. 38.3 %). In logistic regression analyses, atopic skin diathesis was associated with a significantly higher risk of sensitization to methylchloroisothiazolinone/methylisothiazolinone (OR 2.383) and methylisothiazolinone (OR 1.891), thiuram mix (OR 1.614), as well as nickel (OR 1.530), cobalt (OR 1.683), and chromium (OR 2.089). Conclusions Atopic skin diathesis proved to be the most important intrinsic risk factor for contact sensitization to few, specific allergens. Past or present AD was a less relevant variable.
Gesehen am 27.08.2021